2011
DOI: 10.1038/ijo.2011.171
|View full text |Cite
|
Sign up to set email alerts
|

Induction of fatty acid oxidation resists weight gain, ameliorates hepatic steatosis and reduces cardiometabolic risk factors

Abstract: OBJECTIVE: Fatty acid oxidation has been implicated in amelioration of obesity by burning off excessive accumulated lipid. BPR697, a peripheral cannabinoid receptor 1 (CB1) antagonist, elevated fat oxidation without added energy expenditure. Its impact on food intake, body weight changes and metabolic alterations were examined in rats fed standard chow and in diet-induced obesity (DIO) mice. MATERIALS AND METHODS: CB1 agonist-induced hypothermia and analgesia responses were measured to examine the brain activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…The biased biodistribution of BPR0912 was also evident in the food intake experiments of the present study. Our previous examination of a different peripheral CB1R antagonist, BPR0697, suggested that acute blockade of peripheral CB1R was not involved in the food intake suppression observed in animals that were on a SD and treated with this agent . This result has been further supported by investigations of JD5037 , a peripheral CB1R antagonist, and also by our examination of BPR0912 in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The biased biodistribution of BPR0912 was also evident in the food intake experiments of the present study. Our previous examination of a different peripheral CB1R antagonist, BPR0697, suggested that acute blockade of peripheral CB1R was not involved in the food intake suppression observed in animals that were on a SD and treated with this agent . This result has been further supported by investigations of JD5037 , a peripheral CB1R antagonist, and also by our examination of BPR0912 in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Kits to measure serum concentrations of glucose, triglycerides (both from Randox, Crumlin, UK), insulin (Mercodia, Uppsala, Sweden), leptin (R&D Systems, Minneapolis, MN, USA), and non‐esterified fatty acids (Wako, Osaka, Japan) were used according to the manufacturers' instructions. Liver triglycerides were determined as previously described and as detailed in File S1.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in an experiment performed with mice fed a HFD, Lagouge et al demonstrated that chronic treatment with resveratrol did not affect either the RQ or energy intake but resulted in an increased EE that could be, at least in part, responsible for the lower body weight gain and adiposity observed in these animals compared with mice that did not receive this polyphenol [45]. In another study, acute treatment of chow-fed rats with the peripheral cannabinoid receptor 1 (CB1) antagonist BPR697 enhanced fatty acid oxidation and produced a substantial body weight loss without affecting EE and energy intake [46]. Similar results were obtained by Attane and collaborators, whose partially associated the drop in RQ observed in HFD apelin-treated mice with decreased adiposity, although no changes in EE were observed [47].…”
Section: Discussionmentioning
confidence: 92%
“…The latter effect should not be neglected, although this aspect is beyond the scope of this work. It is known that the metabolic changes that occur in the liver as a result of obesity are important mechanisms that underlie development of metabolic syndrome and insulin resistance [120].…”
Section: Discussionmentioning
confidence: 99%